Characteristics of Pore-Throat in Tight Sandstones of the Jurassic Ahe Formation in the Northern Tarim Basin - Tong Lin; Cong Tan; Xing Zhang; Lei Zhao; Hongxing Wei; Lan Wang; Xin Nie; Xu Zeng (Geofluids)
In order to clarify the characteristics of pore-throat in tight sandstone reservoirs in the Dibei area of the Kuqa Depression in the Tarim Basin (Northwest China) and to make clear its impact on reservoir quality and productivity, microscopic observation and quantitative analysis of 310 tight sandstones in the Kuqa Depression are carried out by using various methods. Microscopic observation shows that the shapes of the pores are flat, oval, and long-narrow. A great number of throats connect the nanoscale pores in the form of a network. Quantitative analyses including RCMP (rate-controlled mercury penetration), HPMI (high-pressure mercury injection), NA (nitrogen adsorption), and routine and stress-dependent core analysis show that the peak of pores radius ranges from 125 μm to 150 μm, and the throat radius is in the range of 1 μm-4 μm. The throat space accounts for about 2/3 of the total space of the tight sandstones, which is the major storage space for natural gas. The space shape has a great influence on the reservoir seepage capacity, particularly under the condition of overburden pressure. The pores with throat radius greater than 300 nm have free fluid, and they contribute more than 98% of the reservoir permeability. The pore spaces with throat radius among 300 nm-52 nm can release fluids by reservoir stimulation. The pore-throats with radius<52 nm cannot release the irreducible hydrocarbon fluids. In addition, formation pressure is easy to destroy tight sandstone reservoir. The research results will provide insights into the efficient recovery of natural gas in tight sandstones.